Generic Framework For Handoff In Wireless Sensor Networks With Random Forest Classifier - et. al., B. Sakthivel, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In contemporary world, uninterrupted mobile or wireless communication between the sensor networks or cellular networks is essential for the smoother communication. Cellular networks are embedded with cells in which every cell is providing the services to the connecting end users. But it supports only limited roaming area. Here handoff or handover is the essential service when a user moves one network into another geographical area without any interruption. A handoff is principle of conveying the signal from one cell in cellular network to other network. Due to heavy traffic, handoff may be triggered because more number of users is accessing the same cell. Hence it paves the interrupted service communication, high latency, less throughput among the users. In this paper, we design the generic framework for handling the handoff process with Artificial Intelligence. Besides this framework not only applicable for Mobile scenario, it will be applicable for all kinds of Wireless Sensor Networks (WSN). Utilization of Machine learning algorithms like, Random Forest Classifier and Hadoop Infrastructures are contributing this paper to lead the high features of the Hand over process.